Produção de mudas de tamarindeiro irrigado com água residuária da piscicultura e doses de bioestimulantes naturais de algas marinhas - Cardoso Neto, Raulino (2017)
Wastewater from pisciculture has benn used in irrigation and tested in the production of fruitful seedlings. Seaweeds synthesize plant hormones and there are products based on extracts of macroalgae, which are used commercially as biostimulants to increase agricultural production. The objective of this work was to test the efficiency of the best dose of seaweed extract in the development of tamarind seedlings. The work was carried out, from May to October 2016, at the Federal Rural Semi-Arid University (UFERSA), East Campus, in Mossoró-RN. The substrate used was formulated with 30% manure and 70% soil. The experimental design used was in randomized complete blocks (DBC) in a 2x5 factorial scheme, with four replications, in both experiments: 2 (“Bioestimulante A” – “Bioestimulante B”) x 5 (0 ml L-1, 4 ml L-1, 8 ml L-1, 12 ml L-1 e 16 ml L-1de bioestimulante) on first experiment, on the second, 2 ( “Com Bioestimulante – Sem Bioestimulante”) x 5 (0%, 25%, 50%, 75% e 100% of wastewater from pisciculture). Morphological and physiological characteristics were analyzed. The biostimulant based on A. nodosum (Biostimulant "B"), at the dose 4.0 ml L-1, promoted the greatest increases in the dry biomass of tamarind tree and reached the highest values of total length. Biostimulant based on lithothannium (Bio-A) is superior to biostimulant based on Ascophyllum nodosum (Bio-B), with respect to stomatal conductance and high doses, above 5.54 ml L-1, compromise the photosynthetic rate of tamarind seedlings. High concentrations of wastewater from fish farming promote decline in the following evaluated characteristics: Number of leaves, length of the aerial part, total length, dry mass of the root system, dry mass of the aerial part, total dry mass, stomatal conductance and transpiration. The concentrations used in this experiment (25%, 50%, 75% and 100%) of aquaculture water were very high, not allowing to observe the beneficial effect of water. In this way, we suggest that the next surveys be carried out using smaller concentrations. The biostimulant based on Ascophyllum. nodosum (Biostimulant "B") at the dose 4.0 ml L-1 promoted the greatest increases in the aerial parts and dry biomass of tamarind seedlings